Thermal and electric performances of roll-bond flat plate applied to conventional PV modules for heat recovery. (25th July 2016) - Bombarda, Paola; Di Marcoberardino, Gioele; Lucchini, Andrea; Leva, Sonia; Manzolini, Giampaolo; Molinaroli, Luca; Pedranzini, Federico; Simonetti, Riccardo
Highlights: Three photovoltaic thermal modules were compared. New indexes are defined to assess PVT performances. Roll bond can achieve a higher thermal efficiency when adequately insulated. Advantages of simultaneous electricity and heat production are highlighted. Abstract: Photovoltaic thermal (PVT) modules can increase the renewable energy production by combining the electricity and heat generation. PVT are seen as promising technology for residential applications where the heat can be exploited on site. In this work, the performances of three different PVT modules are evaluated in real operating conditions at the SolarTech LAB . Performance evaluation is conducted both by means of conventional and innovative performance indexes (corrected thermal efficiency and second law efficiency) which are expressly introduced in this work to take into account PVT peculiarities. Dedicated experiments outlined the importance of adopting these peculiar indexes when comparing different PVT modules. In terms of heat recovered, the best roll-bond configuration increases the thermal efficiency by 8% points with respect to the conventional sheet-and-tube one. PVT modules have lower thermal efficiency than commercial only thermal modules (41% vs. 55%), however, the second law efficiency outlines the advantages of producing electricity and heat instead of only heat (16% vs. 2%).